Role of Non-Culture-Based Tests, with an Emphasis on Galactomannan Testing for the Diagnosis of Invasive Aspergillosis - Miceli, Marisa H.; Maertens, Johan (Seminars in Respiratory and Critical Care Medicine, 2015)
An established diagnosis of invasive aspergillus is seldom achieved premortem. Conventional laboratory diagnostic methods such as culture and microscopy, although very useful when positive, are insensitive and time-consuming, resulting in late diagnosis and treatment and contributing to high mortality rates. As a result, routine antifungal prophylaxis and early empirical treatment have been recommended. The use of sensitive and rapid non-culture-based diagnostic assays for the detection of Aspergillus antigens (using commercially available tests to detect galactomannan and 1, 3 β-D-glucan) or detection of genomic DNA sequences may allow a shift in emphasis from empirical to preemptive therapy, especially when substantiated by suggestive radiological findings. These new tools may be used to confirm a presumed diagnosis of invasive aspergillosis, or, when used to screen high-risk patients, may identify an infection at an early stage of disease. Their excellent negative predictive value should convince clinicians to withhold antifungal therapy in patients with no other signs of fungal disease. On the other hand, consecutive positive results should at least trigger a complete diagnostic workup. This article will review the diagnostic utility as well as the pitfalls of using these non-culture-based tools for diagnosing invasive aspergillosis.
Keywords: galactomannan; beta-D-glucan; polymerase chain reaction; Aspergillus; diagnosis; preemptive